Analyst Is Value Engineering On The Construction of Flats For Educators UGM Sleman - Indah Purwanty, Kharisma; Oetomo, Wateno; Djoko Nugroho , Laksono (Devotion : Journal of Research and Community Service, 2023)
The construction of UGM Educator Flats in Sleman Regency has a total area of 7,035.5 m2 consisting of 6 floors in the form of rooms and management rooms for flats and 1 rooftop floor. The problem in implementing the construction of the UGM Educator Flats in Sleman Regency is that the available funds are limited, so value engineering needs to be carried out so that the construction can be completed as expected. Value Engineering aims to obtain the best value for a project or process by defining the functions required to achieve the value objectives and providing these functions at the lowest cost, consistent with the required quality and performance. The results of the study were (1) The work items for the UGM Sleman Educator House building that have the potential to be efficient are floor slab work t=12 cm, roof slab work t=15 cm, stair slab work t=15 cm and beam work. (2) The replacement design alternatives are: a. For beam work items, an alternative is to change formwork purchases to formwork leases, b. For floor slab work items, roof slab work items, stair slab work items, there are 2 alternatives chosen, namely replacing reinforcement with M10 wiremesh and changing formwork purchases to formwork rentals. (3) Cost savings achieved after Value Engineering was carried out by 11.47%, with details of work items as follows: a. Beam work, savings of 3.66%, b. Floor slab work t = 12 cm, savings of 5.55%, c. Roof slab work, t=15 cm, savings of 1.00 %, d. Ladder slab work, t=15 cm, savings of 1.26%. Compared to the Initial Design Budget Plan (RAB) of the project as a whole, the Alternative Design Budget Plan can save costs of 2.843%.